Fetal Doppler changes 1 week after endoscopic equatorial laser for twin‐to‐twin transfusion syndrome: A longitudinal study. (26th February 2018) - Persico, Nicola; D'Ambrosi, Francesco; Fabietti, Isabella; Boito, Simona; Aiello, Elisa; Bulfoni, Alessandro; Ciralli, Fabrizio; Kustermann, Alessandra; Mosca, Fabio; Fedele, Luigi
Abstract: Objective: To investigate sequential Doppler changes in donors and recipients before and 1 week after endoscopic laser for twin‐to‐twin transfusion syndrome (TTTS) and to examine factors that may be associated with such changes. Methods: In TTTS pregnancies undergoing laser treatment, we examined fetal Doppler changes before and 1 week postintervention. Intrauterine death rates and preoperative factors were analyzed in relation to Doppler changes. Results: Among 129 (85.4%) donors surviving at 1 week after laser, there was normalization of umbilical artery flow in 26 (72.2%) of 36 cases with preoperative abnormal Dopplers. In the remaining 10 (27.8%) fetuses, abnormal findings persisted. The rate of later intrauterine death was significantly higher in the latter group (6 of 10, 60.0%) compared with fetuses in which Doppler findings normalized (4 of 26, 15.4%; P  < .05), with no difference in the rate of severe donor growth restriction between the 2 groups (80.0% vs 65.4%, respectively; P  = .688). Conclusions: In about 70% of TTTS donors with preoperative abnormal umbilical artery Doppler, there was normalization 1 week after endoscopic laser. The incidence of fetal growth restriction was not significantly different in donors with persistence of Doppler abnormalities compared with those with normalized findings. Abstract : What's already known about this topic? In twin‐to‐twin transfusion syndrome requiring laser treatment, preoperative umbilical artery abnormalities in donor fetuses are associated with an increased risk of postoperative fetal demise. Less is known about changes in fetal Dopplers 1 week postlaser and their clinical significance. What does this study add? In about 70% of TTTS donors with abnormal umbilical artery Doppler, there was normalization of flow 1 week after endoscopic laser. In our series, the incidence of fetal growth restriction was not significantly different in donors with persistence of Doppler abnormalities compared with those with normalized findings.